Behavioural Intention of Using E-Learning System: A Bibliometric Perspective - Alasmari, Manswr; Brika, Said; Onn, Wong Chee; Al-Ahmari, Dhafer; Al-Mawlid, Abdulrahman (Journal of Ecohumanism, 2024)
The Unified Theory of Acceptance and Use of Technology (UTAUT) has evolved to be a very important theory in the acceptance and usage of learning technologies. This paper does a bibliometric study on UTAUT concerning learning environments based on the Scopus database from 2004 to 2025. By the use of sophisticated bibliometric instruments, procedures, and methods such as citation analysis, co-authorship mapping, and keyword co-occurrence visualization, this paper presents an extensive analysis of UTAUT in learning. The analysis seeks to determine the trends and the contributors and shifts in the research focus in the last twenty years. It draws attention to such a factor as the practical application of UTAUT in learning studies and its critical importance in understanding the use of educational technologies. UTAUT continues to advance as more usage of its concept is illustrated in learning environments with newer ideas that address recent developments such as mobile learning and digital literacy being integrated. In addition, through this method, the paper maps out the chronological development of UTAUT within the scope of learning and suggests several potential directions for future studies after identifying existing challenges. The results substantiate the importance of UTAUT in the conduct of technology diffusion issues, with an emphasis on educational change and the development of pedagogical ideas in the custody of new technologies.